DIALECTICS AND THE EVOLUTION OF THOUGHT IN HISTORY: A PHILOSOPHICAL PERSPECTIVE OF HEGEL - Pratama, Putra (Transpublika Publisher, 2024)
This article explores the concepts of history and dialectics in the perspective of Hegel's philosophy. History, defined as a science that studies concrete events based on the processes that occur, is understood through two key elements: events and dialectics. Events are absolute and objective, while dialectics is a communication process involving thesis, antithesis and synthesis. In Hegel's view, history not only records what happened but also describes the evolution of human thought through a dialectical process. According to Hegel: genuine history, reflective history, and philosophical history. Genuine history, as practiced by Herodotus and Thucydides, includes direct narration of events. Reflective history, outlined in Hegel's works such as the